Can government subsidy promote the light-blue fishery upgrade to deep-blue fishery? - Zheng, Shan; Zhang, Ying (Frontiers in Marine Science, 2024)
The expansion of fishery development space from offshore to deep sea has become an inevitable requirement for countries to cope with environmental constraints and food security. This paper establishes a cooperative development model of deep-blue fishery involving the government, fishery enterprises and consumers, then constructs an evolutionary game and simulation model to analyze the deep-blue fishery subsidy strategy of government. The results show that government subsidy can promote the development of deep-blue fishery from demand and supply side. The probability of government subsidy has a positive influence on fishery enterprises developing the deep-blue fishery and consumers purchasing the deep-blue fishery products. According to the cost-benefit changes of the government, fishery enterprises and consumers, the evolutionary game system achieves different steady states and the government also generates different optimal subsidy strategies. From the evolutionary law under different subsidy amounts, the amount of government subsidy is not the more the better. From the evolutionary results of subsidizing different subjects, compared with subsidizing consumers, subsidizing fishery enterprises can better promote the development of deep-blue fishery.